Densidad y distribución de ungulados silvestres en la reserva ecológica el Edén, Quintana Roo, México - González-Marín, Rosa María; Gallina, Sonia; Mandujano, Salvador; Weber, Manuel (Instituto de Ecología, A.C., 2008)
The forests of the northeast Yucatan Peninsula supports wild ungulate populations such as the white-tailed deer (Odocoileus virginianus (Hays 1874), brocket deer (Mazama americana Erxleben 1777 and M. pandora Merriam 1901) and collared pecari (Pecari tajacu Merriam 1901). For its conservation and use, it is necessary to know the current status of wild ungulates populations. Basic ecological aspects such as density and distribution of the ungulate populations in different vegetation types were evaluated. The study area was El Edén Ecological Reserve (EER), located in the northern Yucatan Peninsula in Quintana Roo State, Mexico. The method used to assess ungulate density and distribution was the strip transect counts. The transects were set on the existing roads and footpaths. Using GIS, the habitat and five vegetation types were classified: secondary vegetation (acahual), tropical evergreen forest, tintales, savanna of palms and aquatic vegetation. Thirty eight observations of white-tailed deer were obtained, 14 of brocket deer and 6 groups of pecaries in 293.4 km of routes. The observation period was between September 2004 and April 2005 (six months of sampling). The absolute density of the white-tailed deer was 5,5 ± 4,1 ind/km2, for the pecari was 1,9 ± 0,8 ind/km2 or 0,2 ± 0,1 herd/km2 and for brocket deer was 1,7 ± 1,8 ind/km2. Acahual was the vegetation type where white-tailed deer and collared pecari were found. This is the first time that M. americana was registered in this region of the State. These results suggest the important role that have the EER to conserve ungulates, nevertheless the continued risk of hurricanes and fires. The white-tailed deer population is high compared with other tropical zones.